ANALYZE OF STUDENT LEARNING OUTCOMES USING PROBLEM BASED LEARNING AND DISCOVERY LEARNING REVIEWED FROM HOTS - Tiara Ritonga; Ahmad Nasir Pulungan; Retno Dwi Suyanti; Nora Susanti; Makharany Dalimunthe (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This study aims to determine whether there is a difference between the learning outcomes of students taught with Problem Based Learning and Discovery Learning models in terms of higher order thinking skills (HOTS) on chemical equilibrium material. The study population was all students of class XI IPA SMA Negeri 11 Medan. The sample in this study consisted of 2 experimental classes. The instrument used in the study was a test instrument. Before hypothesis testing, normality test and homogeneity test were conducted first. In the normality and homogeneity test in each class sample, the results showed that the data were normally distributed and homogeneous. Furthermore, the N-Gain test was carried out, the results of data processing showed that the increase in learning outcomes in experimental class I was in the medium category, and in experimental class II was in the high category. Based on the results of data processing with the Independent Sample T-Test test for hypothesis testing, the Sig value is obtained. = 0.017 at the 5% significance level (α = 0.05). Because the value of Sig. α (0.05), then in this study the alternative hypothesis (Ha) is accepted.